PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA SEKTOR JASA DI GRAFIKA OFFSET PONTIANAK - Oktaliani, Ummi; Hijriah, Amanah (Jurnal KIAFE, 2023)
The service sector plays a very important role in the Indonesian economy. One phenomenon regarding the service sector is the continued growth of companies in the service industry, one of which is printing companies. This study aims to understand how to manage demand and production capacity from Offset Graphics. The method used in this research is descriptive qualitative method with the aim of describing, exploring, and obtaining information related to problems and phenomena that occur so that they can become information for solving problems that occur. This study uses observation, interviews, and literature studies as data collection techniques. With the phenomenon that occurs which is often related to delays in fulfilling consumer requests, the hope of this research is to increase demand for goods in Offset Graphics, namely to improve production quality by implementing company Standard Operating Procedures (SOP) in production activities and continuing to control inventory through FIFO method.